COMPARATIVE ANALYSIS OF THE COST OF PRODUCTION AND ITS IMPLICATIONS ON SELLING PRICES AND PROFITABILITY IN MICRO, SMALL AND MEDIUM ENTERPRISES TEMPE UCOK - Ziska Ayunda; Khairunnisa Almadany; Syahril Syahril (Ikatan Dosen Menulis, 2026)
Accurate production-cost measurement determines the quality of selling-price decisions and profitability assessment in microenterprises. This study compares the production cost recorded by Tempe Ucok with the full costing method and analyzes its implications for alternative selling prices and estimated profitability. A quantitative descriptive case-study design was employed using interviews, direct observation, and cost documentation for February and March 2025. Costs were classified into direct materials, direct labor, variable overhead, and fixed overhead. The enterprise recorded production costs of IDR 17,550,000 in February and IDR 18,720,000 in March. After equipment depreciation was included, full-costing production costs increased to IDR 17,635,415 and IDR 18,805,415, equivalent to IDR 1,464.74 and IDR 1,457.78 per unit. Scenario analysis using cost markups of 10%, 15%, and 20% produced theoretical selling-price alternatives of approximately IDR 1,611-IDR 1,758 per unit in February and IDR 1,604-IDR 1,749 in March. The findings show that comprehensive cost recognition provides a more consistent pricing basis and reduces the risk of overstating profitability. Because actual selling prices, units sold, inventory balances, and revenue were not available, profitability is presented as a scenario-based estimate rather than the enterprise's realized profit.